2012
DOI: 10.3233/jad-2011-111415
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Increases Ventricular Volume in a Rabbit Model of Alzheimer's Disease

Abstract: One of the hallmarks of Alzheimer’s Disease is a significant increase in ventricular volume. To date we and others have shown that a cholesterol-fed rabbit model of Alzheimer’s Disease displays as many as fourteen different pathological markers of Alzheimer’s Disease including amyloid β accumulation, thioflavin-S staining, blood brain barrier breach, microglia activation, cerebrovasculature changes and alterations in learning and memory. Using structural magnetic resonance imaging at 3T we now report that chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 62 publications
8
20
0
Order By: Relevance
“…The cholesterol-fed rabbit model of AD shows a multitude of pathological findings similar to those seen in AD patients including Aβ deposits, neurofibrillary tangles, apoptosis, microglia activation, and increased ventricular volume [12, 13, 39, 40] as well as cognitive deficits [1721]. Here we also demonstrated that a high-cholesterol diet is associated with significant levels of neurodegeneration in the hippocampus.…”
Section: Discussionsupporting
confidence: 64%
“…The cholesterol-fed rabbit model of AD shows a multitude of pathological findings similar to those seen in AD patients including Aβ deposits, neurofibrillary tangles, apoptosis, microglia activation, and increased ventricular volume [12, 13, 39, 40] as well as cognitive deficits [1721]. Here we also demonstrated that a high-cholesterol diet is associated with significant levels of neurodegeneration in the hippocampus.…”
Section: Discussionsupporting
confidence: 64%
“…Many of the same networks found in humans, non-human primates, and rodents are also found in the rabbit. Our findings provide the first examination of the rabbit as a potential animal model for translational research studying neural networks and provide the baseline data for changes that may occur during different behavioral states or disease states such as Alzheimer's disease (Deci et al, 2012; Liu et al, 2012; Perez-Garmendia et al, 2014; Schreurs et al, 2013). …”
Section: Discussionmentioning
confidence: 96%
“…Importantly, although we continued to see higher levels of beta amyloid immunoreactivity with copper added to the drinking water of cholesterol-fed rabbits compared to those on distilled water, there was no evidence of extracellular beta amyloid plaques. This was even true when we doubled the copper concentration in the drinking water to 0.24 ppm although, in that case, the cortical levels of beta amyloid immunoreactivity were significantly higher in chow-fed rabbits given 0.24 ppm copper compared to those given distilled water suggesting that copper by itself was having an effect on beta amyloid accumulation [61]. …”
Section: Cholesterol Copper and Beta Amyloidmentioning
confidence: 99%
“…At the conclusion of many of our behavioral experiments, we began structural MRI imaging of the rabbits' brains to explore the effects of cholesterol and copper on rabbit ventricular volume [61, 67] and cerebrovascular diameter [67]—indices that have been noted to change in patients with AD [6871]. The four panels of Figure 4 show structural MRI scans of rabbits that received normal chow and distilled water (a), normal chow and 0.12 ppm copper added to the distilled water (b), 2% cholesterol and distilled water (c), and 2% cholesterol and copper (d), with insets that show the area of the third ventricle.…”
Section: Imaging the Effects Of Cholesterol And Coppermentioning
confidence: 99%
See 1 more Smart Citation